Determinant Factors Relating To Exclusive Breastfeeding Practices In The Working Area Of Sambi Puskesmas - nerawati, nawang (Bachelor Nutrition Study Program - Faculty of Medicine, 2024)
Tempursari Village, in September 2023 will have exclusive breastfeeding coverage of 40% for male babies and 33.3% for female babies. Then for Demangan Village, it is 50% for male babies and 40% for female babies. This research aims to understand the determinant factors related to the practice of exclusive breastfeeding in the Sambi Work Area. The research method used is analytical observational, with a case control approach. The research, which was conducted in February 2024, was carried out at Posyandu in both sub-districts. The sampling technique was cluster random sampling with a total sample of 64 respondents, with a 1:1 ratio of cases to controls. Meanwhile, the data analysis carried out was univariate analysis and bivariate analysis with the chi square test. There was a relationship between mother's age (p=0.005), mother's attitude (p=0.0001), education level (p=0.0001), family support ( p=0.004), working mother's status (p=0.0001) and exclusive breastfeeding practices in Demangan and Tempursari subdistricts. And there is no relationship between the mother's psychological condition (p=0.07) and exclusive breastfeeding practices in Demangan and Tempursari subdistricts. . There is a relationship between maternal age, maternal attitudes, education level, family support, and working maternal status with the practice of exclusive breastfeeding. There is no relationship between the psychological condition of the mother and the practice of exclusive breastfeeding in the Sambi Community Health Center working area.